Impact of cloud cover in temperatures in Iraq - Shaker Shnishal, Balsam (Al-Adab Journal, 2019)
The current research idea was to determine the effect of the low-altitude cloud cover at a height of less than 2500 meters from the surface of the earth at normal temperature variations during the observations )00( and )1200( GMT and compare them with the temperature of the cloudless days. Repeat the nine low clouds and determine their temporal percentages during the period (1992-2002) and selectively select four climate monitoring stations distributed geographically in a manner covering all parts of Iraq. Statistical model (The correlation of the Hirraceae ) was applied to emphasis this relationship, So It appeared that there’s a strong relationship between the effect of the cloud presence or not on temperature rates that connected between (Ar-Rutbah and Al-Basra) stations during the observation (00)GMT. While (Baghdad and Al-Basra) stations were connected during the observation (1200)GMT. While (summer and autumn) were connected by repetition of the same kind of clouds in them and enjoyed both (winter and spring) with a group of its own far from other seasons in each of day and night monitoring.